Ullrich Congenital Muscular Dystrophy (UCMD): Clinical and Genetic Correlations - BOZORGMEHR, Bita; KARIMINEJAD, Ariana; NAFISSI, Shahriar; JEBELLI, Bita; ANDONI, Urtizberea; GARTOUX, Corine; LEDEUIL, Celine; ALLAMAND, Valérie; RICHARD, Pascale; KARIMINEJAD, Mohammad-Hassan (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Bozorgmehr B, Kariminejad A, Nafissi Sh, Jebelli B, Andoni U, Gartioux C, Ledeuil C, Allamand Y, Richard P, Kariminejad MH. Ullrich Congenital Muscular Dystrophy (UCMD):Clinical and Genetic Correlations. Iran J Child Neurol. 2013 Summer; 7(3): 15-22. Objective: Ullrich congenital muscular dystrophy (UCMD) corresponds to the severe end of the clinical spectrum of neuromuscular disorders caused by mutations in the genes encoding collagen VI (COL VI). We studied four unrelated families with six affected children that had typical UCMD with dominant and recessive inheritance. Materials & Methods Four unrelated Iranian families with six affected children with typical UCMD were analyzed for COLVI secretion in skin fibroblast culture and the secretion of COLVI in skin fibroblast culture using quantitative RT–PCR (Q-RT-PCR), and mutation identification was performed by sequencing of complementary DNA. Results COL VI secretion was altered in all studied fibroblast cultures. Two affected sibs carried a homozygous nonsense mutation in exon 12 of COL6A2, while another patient had a large heterozygous deletion in exon 5-8 of COL6A2. The two other affected sibs had homozygote mutation in exon 24 of COL6A2, and the last one was homozygote in COL6A1. Conclusion In this study, we found out variability in clinical findings and genetic inheritance among UCMD patients, so that the patient with complete absence of COLVI was severely affected and had a large heterozygous deletion in COL6A2. In contrast, the patients with homozygous deletion had mild to moderate decrease in the secretion of COL VI and were mildly to moderately affected. References 1. Voit T. Congenital Muscular Dystrophies Brain Dev 1998;20(2): 65-74. 2. Ullrich OZ Ges. Scleroatonic Muscular Dystrophy. Neurol Psychiatr 1930;126:171-201. 3. Ullrich O. Monatsschr. Kinderheilkd 1930;47:502-10. 4. Mercuri E, Yuva Y, Brown SC, Brockington M, Kinali M, Jungbluth H, et al. Collagen VI involvement in Ullrich Syndrome: A Clinical, genetic and Immunohistochemical study. Neurology 2002;58(9):1354-9. 5. Lampe AK, Bushby KM. Collagen VI related muscle disorders. J Med Genet 2005;42(9):673-85. 6. Mercuri E, Muntoni F. Congenital Muscular Dystrophies. In: Emery AEH, editors. The muscular dystrophies. Oxford: Oxford University Press: 2001. p. 10-38. 7. Furukawa T, Toyokura Y. Congenital Hypotonic-Sclerotic muscular dystrophy. J Med Genet 1977;14(6):426-9. 8. Nonaka I, Une Y, Ishihara T, Miyoshino S, Nakashima T, Sugita H. A clinical and histological study of Ullrich’s disease (congenital atonic-sclerotic muscular dystrophy). Neuropediatrics 1981; 12(3):197-208. 9. Pan TC, Zhang RZ, Sudano DG, Marie SK, Bonnemann CG, Chu ML. New molecular mechanism for Ullrich Congenital Muscular Dystrophy: A heterozygous inframe deletion in the COL6A1 gene causes a severe phenotype. Am J Hum Genet 2003;73(2):355-69. 10. Baker NL, Morgelin M, Peat R, Goemans N, North KN, Baterman JF, et al. Dominant Collagen VI Mutations are a common cause of ullrich congenital muscular dystrophy. Hum Mol Genet 2005;14(2]):279-93. 11. Pace RA, Peat RA, Baker NL, Zamurs L, Morgelin M, Irving M et al. Collagen VI glycine mutations: Perturbed assembly and a spectrum of clinical severity. Ann Neurol 2008;64(3):294-303. 12. Bethlem J, Wijngaarden GK. Benign myopathy, with autosomal dominant inheritance. A report on three pedigress. Brain 1976;99(1):91-100. 13. Gualandi F, Urciuolo A, Martoni E, Sabatelli P, Squarzoni S, Bovolenta M, et al Auotosomal recessive Bethlem myopath. Neurology 2009;73(22):1883-91. 14. Foley AR, Hu Y, Zou Y, Columbus A, Shoffiner J, Dunn DM, et al. Autosomal recessive Bethlam Myopathy. Neuromuscular Disord 2009;19(10):813-7.